Study of Implementation of Fiscal Correction as an Effort to Efficiently Pay Income Tax Payable for Corporate Taxpayers - R Taufik Hidayat; Frengki Panangian; Andi Muhammad Sadli (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
Tax payment is one of any cost that will reducing margin contributions. To achieve tax payment efficient, legal withholding tax, and increase financial performance we need Tax Planning for reducing tax cost overall. One of tax planning is commercial income correction to the fiscal income statement in Income Tax. Fiscal Correction is correcting the commercial income statement to the fiscal income statement which accept by tax authorities. Fiscal Correction of Income Statement is legal point for withholding tax payment as per Tax Regulation (Undang-undang RI) No.28/2007 and No.36/2008. Application of Tax Planning with Fiscal Correction reducing tax payment from Rp. 59.419.480 to Rp. 39.497.348,- that mean will save Rp.19.922.132 of tax payment. Keywords : Fiscal Correction, Tax Planning, Saving tax payment.